Kulturowe czy polityczne wojny domowe? Mit i rewolucja w prawicowej poezji dwudziestolecia międzywojennego - Kuciński, Paweł (Załącznik Kulturoznawczy, 2021)
The article presents the history of the concepts of myth and revolution in political poetry in the 1930s. Under the pressure of politics, these terms lost their meaning assigned by tradition. This observation leads to conclusions of a more general nature: the essence of involvement and the role of literature as an intermediary between politics as a historical source and politics as a paradoxically non-ideological activity. Thus, literature as an institution mediates in immunizing politics, especially radical politics. Becoming a serious element of the order dictated by the cultural canons existing in equilibrium and their reinterpretations.